Characterization of an emergent clone of enteroinvasive Escherichia coli circulating in Europe. (March 2016) - Michelacci, V.; Prosseda, G.; Maugliani, A.; Tozzoli, R.; Sanchez, S.; Herrera-León, S.; Dallman, T.; Jenkins, C.; Caprioli, A.; Morabito, S.
Abstract: Enteroinvasive Escherichia coli (EIEC) cause intestinal illness indistinguishable from that caused by Shigella, mainly in developing countries. Recently an upsurge of cases of EIEC infections has been observed in Europe, with two large outbreaks occurring in Italy and in the United Kingdom. We have characterized phenotypically and genotypically the strains responsible for these epidemics together with an additional isolate from a sporadic case isolated in Spain. The three isolates belonged to the same rare serotype O96:H19 and were of sequence type ST-99, never reported before in EIEC or Shigella. The EIEC strains investigated possessed all the virulence genes harboured on the large plasmid conferring the invasive phenotype to EIEC and Shigella while showing only some of the known chromosomal virulence genes and none of the described pathoadaptative mutations. At the same time, they displayed motility abilities and biochemical requirements resembling more closely those of the non-pathogenic E. coli rather than the EIEC and Shigella strains used as reference. Our observations suggested that the O96:H19 strains belong to an emerging EIEC clone, which could be the result of a recent event of acquisition of the invasion plasmid by commensal E. coli.